Profilaxis antibiótica en cirugía e instrumentación urológica. - Hernández Ajubita, H.; Moreno Sierra, Jesús; Resel, Luis; Senovilla Pérez, J.L.; Silmi Moyano, A. (Clínicas Urológicas de la Complutense, 1997)
Sin resumen